Age modifies both the maximal temperature and inflammatory response in patients with SARS-CoV-2 infection. Issue 3 (2022) - Crooks, Colin J; West, Joe; Morling, Joanne R; Simmonds, Mark; Juurlink, Irene
No abstract available